Update Breast Cancer 2017 - implementation of novel therapies = Update Mammakarzinom 2017 - Etablierung neuer zielgerichteter Therapien - Lux, Michael Patrick; Wallwiener, Markus; Schneeweiss, Andreas (Geburtshilfe und Frauenheilkunde, 2017)
In recent years, numerous new therapy options for patients with breast cancer have been developed in clinical studies, with some options already approved for routine treatment. As the speed at which innovations are introduced increases, the importance of conferences also increases, as conferences are where the data underpinning new therapies are usually presented for the first time. This review looks at publications of the ASCO (American Society of Clinical Oncology) and ESMO (European Society of Medical Oncology) conferences in 2017, summarizes them and evaluates them in the context of existing data. The focus is on new insights for neoadjuvant therapy and new treatment options in the metastatic setting, such as the use of CDK4/6 inhibitors or PARP inhibitors. The first results of treatments with checkpoint inhibitors are presented. With the patent expiry of trastuzumab, a number of study results for trastuzumab biosimilars have also been published. The digitization of patient care provides the first results on quality of life and prognosis of patients with advanced cancer. Digital communications between patients and physicians are being evaluated in several studies in Germany. As the discussion about patient-relevant endpoints for patients in the metastatic setting continues, overall survival rates from studies of big endocrine-based therapies are urgently needed. Preliminary analyses of small study cohorts offer initial insights. In the context of improving patient care, in the coming years, questions will center on which patients particularly benefit from certain therapies and which patients need particular protection from specific side effects. Questions about these predictors are raised in many scientific projects as attention increasingly focuses on this topic. , In den letzten Jahren sind zahlreiche neue Therapieoptionen für die Patientin mit einem Mammakarzinom in klinischen Studien entwickelt worden und teilweise zur Zulassung gekommen. Bei zunehmender Geschwindigkeit neuer Innovationen nimmt die Bedeutung von Kongressen zu, auf denen meist zum ersten Mal Daten zu den entsprechenden Therapien präsentiert werden. Diese Übersichtsarbeit greift Veröffentlichungen der Kongresse ASCO (American Society of Clincial Oncology) und ESMO (European Society of Medical Oncology) aus dem Jahr 2017 auf und fasst sie im Kontext bestehender Daten zusammen. Der Fokus liegt auf Erkenntnissen aus der neoadjuvanten Situation und Neuigkeiten aus der metastasierten Situation, wie der Einsatz von CDK4/6-Inhibitoren oder PARP-Inhibitoren. Des Weiteren werden erste Ergebnisse zur Behandlung mit Checkpoint-Inhibitoren dargestellt. Bei baldigem Patentablauf von Trastuzumab sind zudem einige Studienergebnisse zu Trastuzumab-Biosimilars veröffentlicht worden. Auch die Digitalisierung der Patientenversorgung liefert erste Ergebnisse in Bezug auf Lebensqualität und Prognose von Patientinnen mit fortgeschrittener Krebserkrankung. Die digitale Kommunikation zwischen Patientin und Ärztin bzw. Arzt wird auch in Deutschland in einigen Studien untersucht. Bei anhaltender Diskussion über patientenrelevante Endpunkte für Patientinnen in der metastasierten Situation werden die Gesamtüberlebensdaten für die großen endokrin basierten Studien dringend erwartet. Erste Einblicke liefern vorläufige Analysen an kleinen Studienkollektiven. Im Rahmen der Patientenversorgung werden in den nächsten Jahren die Fragen aufkommen, welche Patientinnen besonders von bestimmten Therapien profitieren und welche vor besonders relevanten Nebenwirkungen geschützt werden können. Die Frage nach diesen Prädiktoren begleitet viele wissenschaftliche Projekte und bekommt eine besondere Aufmerksamkeit.